2015
DOI: 10.1093/ckj/sfv017
|View full text |Cite
|
Sign up to set email alerts
|

Cesium-associated hypokalemia successfully treated with amiloride

Abstract: Self-treatment of cancer with cesium chloride, despite proven lack of efficacy, continues to produce serious adverse effects. Among these is hypokalemia predisposing to life-threatening arrhythmia. The mechanism of cesium-associated hypokalemia (CAH) has not been described. We report urinary potassium wasting responsive to amiloride therapy in a cancer patient with CAH, and discuss possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…[11][12][13][14][15] Importantly, Cai et al 15 found a significant reduction in serum levels of the alkali metal cesium in individuals with SCZ in comparison with healthy controls. This may be important because cesium shares some similarities with potassium, and therefore may interfere with potassium metabolism, 16 while a single nucleotide polymorphism (SNP) in the KCNH2 gene, which encodes the pore-forming subunit of potassium channels, has been associated with SCZ and with cognitive impairments. 17 Moreover, cesium, rhenium, and rubidium were previously assayed in sera of patients with another immune-inflammatory illness, namely rheumatoid arthritis, with cesium found to be decreased in patients as compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Importantly, Cai et al 15 found a significant reduction in serum levels of the alkali metal cesium in individuals with SCZ in comparison with healthy controls. This may be important because cesium shares some similarities with potassium, and therefore may interfere with potassium metabolism, 16 while a single nucleotide polymorphism (SNP) in the KCNH2 gene, which encodes the pore-forming subunit of potassium channels, has been associated with SCZ and with cognitive impairments. 17 Moreover, cesium, rhenium, and rubidium were previously assayed in sera of patients with another immune-inflammatory illness, namely rheumatoid arthritis, with cesium found to be decreased in patients as compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Cai et al found a significant reduction in serum levels of the alkali metal cesium in SCZ patients in comparison with healthy controls 15 . This may be important because cesium shares some similarities with potassium and, therefore, may interfere with potassium metabolism 16 while there is some evidence that the KCNH2 SNP, which encodes the pore-forming subunit of potassium channels, is associated with schizophrenia and with cognitive impairments 17 . Moreover, cesium, rhenium, and rubidium were previously assayed in sera of patients with another immune-inflammatory illness, namely rheumatoid arthritis, and of those three metals cesium was found to be decreased in patients as compared with healthy controls 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Metallic cesium form is used in a variety of products for example, Atomic Clocks, carbon dioxide purification; and ion cesium form is used in Biotechnology and Medicine for example, purification of nucleic acids, i.e., RNA and DNA viruses (22).Cesium chloride for cancer treatment has never been approved by the US Food and Drug Administration (FDA). It may cause serious cardiac arrhythmias, prolonged QTC interval (24), hypokalemia (25) and accumulation in brain (26), and has impact on Thyroid Function (27).Silver and Cesium determination in water is performed by different methods. The present study measured the level of Cesium and Silver in drinking water by FGAAS which is a micro-amount sample analysis method with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%